Modern Trends in the Development of Mediation Agreements - Sultonov , Bobirxon; Halimov , Rahimjon (GLOBAL SCIENTIFIC CONFERENCE ON MULTIDISCIPLINARY RESEARCH, 2026)
This empirical investigation analyzes the modern evolution of mediation agreements within civil and commercial jurisprudence. Evaluating 420 disputes resolved between 2021 and 2025, the study quantifies the shift toward consensual resolution. Integration of pre-trial mediation reduced judicial backlogs by 68.4%. Furthermore, agreements fortified by modern standards (e.g., the Singapore Convention) demonstrated an 89.2% voluntary compliance rate, vastly outperforming traditional court rulings (54.3%). The data confirms mediation agreements are transitioning from standard civil contracts into independently enforceable instruments. Reforming national codes to grant them immediate writ of execution status is a structural necessity to optimize restorative justice.